37.5k views
3 votes
2x + 3y = 3 and x + 6y = -3

User Krizzo
by
5.4k points

2 Answers

5 votes
Y=-2/3x+ 3 y=-1/6x-3 hope this helps if your finding slope. You subtract the x to the other side then divide the y
User James Wise
by
5.0k points
5 votes

Answer:

(3, - 1 )

Explanation:

Given the 2 equations

2x + 3y = 3 → (1)

x + 6y = - 3 → (2)

Multiplying (1) by - 2 and adding to (2) will eliminate the y- term

- 4x - 6y = - 6 → (3)

Add (2) and (3) term by term eliminating y

- 3x = - 9 ( divide both sides by - 3 )

x = 3

Substitute x = 3 into either of the 2 equations and solve for y

Substituting into (2)

3 + 6y = - 3 ( subtract 3 from both sides )

6y = - 6 ( divide both sides by 6 )

y = - 1

Solution is (3, - 1 )

User MarkPlewis
by
4.8k points